THE ROLE OF MOSLEM SOCIETIES’S LEADERSHIP IN PERSPECTIVE OF NATIONAL INTEGRATION: A CASE STUDY IN PEGAYAMAN VILLAGE, BULELENG DISTRICT, BALI - I Nyoman Mardika (Universitas Warmadewa, 2019)
Muslim communities which is located in Pegayaman Village, in Buleleng Regency, have a unique and ambivalent position. Nationally, they are part of the majority Muslim communities in Indonesia. However, since they located at Buleleng regency which is a Hindu majority, the communities certainly becomes a minority group. The Muslim community of Pegayaman can live in harmony and be able to integrate with other community as a minority. In the national integration of the Muslim Pegayaman community is able to blend with other communities without losing their cultural identity. This is inseparable from the system of values, beliefs amd cultural (religious) identity and leadership in the village. The concept was able to bring the Pegayaman Muslim community to maintain national intehration and keep them away from disintegration process.